Analisis Pengelolaan Limbah Medis Padat Menurut Permenkes No. 7 Tahun 2019 Di Rumah Sakit Tahun 2022 - Linda Fitrianingsih; Mohamad Yaser (Lembaga Pengembangan Kinerja Dosen, 2023)
Hospital waste is waste generated from hospital activities. Indonesia is estimated to produce Hospital Medical Waste of 376,089 tonnes/day. So it is necessary to have efforts to manage solid medical waste in accordance with PERMENKES No. 7 of 2019. The purpose of this research is that the management of solid medical waste at Karya Medika Bantar Gebang Hospital can be carried out properly. This research method uses a descriptive research type method with a qualitative approach. The results of this study in waste management include human resources, facilities and infrastructure, policies that greatly influence the solid medical waste management process. There are still facilities and infrastructure that are not in accordance with PERMENKES No. 7 of 2019 because the trolly itself has not been equipped with a symbol and the color is not distinguished for medical waste and non medical waste trolleys which are still the same. The medical waste management process is in the form of appropriate sorting stages, appropriate container stages, inappropriate transportation stages because waste is still found scattered during transportation because waste exceeds ¾ plastic waste packaging, storage is not appropriate because there is no room temperature in storage, management by a third party is appropriate. The conclusion in terms of facilities and infrastructure, the process of transportation, storage is not in accordance with PERMENKES No. 7 of 2019. Suggestions for increasing training that is more specific to waste management so that officers can understand the waste management process properly and correctly according to the SPO that has been made.